Comparison of the effectiveness of schema therapy and therapy based on acceptance and commitment ACT in reducing anxiety, loneliness and tendency to addiction among male adolescents with divorced parents. - Habibian, Maryam; Poorshirazi, Kimia; Ilghami Azar, Nazanin; Faniani, Fatemeh; Shahi Noori, Bahareh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2021)
Background and Aim: Life after parents’ divorce seems impossible for many children. Children of divorce will experience new negative emotions from the day of divorce onwards. These feelings are so fluctuating that sometimes they are confused and startled by the oppositeness of these feelings, and they will suffer from common feelings such as anxiety, loneliness, and tendency to addiction. Therefore, the aim of the current research was to compare the effectiveness of schema therapy and acceptance and commitment ACT therapy in reducing anxiety, loneliness and the tendency to addiction in male adolescents with divorced parents. Methods: The present research was semi-experimental with a pre-test and post-test design with a control group, and the statistical population was male teenagers with divorced parents in Qom city, 30 male teenagers were selected and randomly divided into three experimental and control groups. The research tools were Beck’s anxiety questionnaire (1990), Russell et al.’s (1980) loneliness questionnaire, Wade and Butcher’s (1992) addiction tendency questionnaire. The experimental group of schema therapy underwent intervention for 8 sessions and the experimental group of therapy based on acceptance and commitment underwent intervention for 10 sessions of 90 minutes. Results: The results showed that schema therapy and therapy based on acceptance and commitment were effective on anxiety, loneliness and tendency to addiction in adolescent boys with divorced parents (P<0.05). Conclusion: The results showed that both approaches are equally effective in reducing anxiety, feelings of loneliness, and the tendency to addiction in teenagers, and it is recommended to use these two approaches as a starting point for intervention.